Factors Associated with Malaria Infection among Head Porters in Agbogbloshie Market in the Greater Accra Region of Ghana. (29th October 2020) - Kwofie, Patience; Tetteh, John; Akakpo, Reindorf Elijah; Sarfo, Bismark
Abstract : Background . Head porters constitute the mobile population who are at an increasing risk of being infected with malaria. They move around the city to carry out their duties with no accommodation. Therefore, they sleep wherever they find themselves in the evening and do not benefit from most of the malaria intervention programs such as the use of long-lasting insecticide net. The inability to identify them because they are mobile means that they can continue to drive malaria transmission even if malaria in the general population is controlled. Objectives . This study assessed the factors associated with malaria infection among head porters in the Agbogbloshie market in the Greater Accra Region of Ghana. Method . A total of 218 head porters were recruited from the Agbogbloshie market, and blood samples were collected from participants to test for malaria parasite infection using Rapid Diagnostic Test (RDT) and microscopy and were interviewed using a closed-ended questionnaire. The data were analyzed using Stata version 15. Simple descriptive statistics, Pearson chi-square, and Multiple Logistic Regression were performed with significance set at <0.05. Result . The study revealed 12% (CI   95 % = 8.2 ‐ 16.9 ) and 9.6% (CI   95 % = 6.3 ‐ 14.4 ) infection of malaria using RDT and microscopy, respectively. Plasmodium falciparum (21/218) was the main parasite detected in all positive blood samples. Age and marital status are significant factors associated with malaria infection among head porters. Age group 40 years and above had 89% (AOR   0.11   CI   95 % = 0.01 ‐ 0.98 ) reduced odds of getting malaria compared to those below 20 years, while those who are single are 3.52 times more likely to be infected with malaria compared with those who are married (AOR   95 % CI = 3.52   1.13 ‐ 10.92 ). Conclusion . This study concludes that the increasing age of head porters significantly decreased the probability of malaria infection, while head porters who are single have greater odds of being infected with malaria. Age and marital status are important factors to be considered for malaria intervention programs in head porters.